(untitled) (Costos y Gestión, 2024)
Society is undergoing the fourth industrial revolution, characterized by digital transformation and the interconnection of intelligent systems. This change has impacted various areas such as the economy, politics, society, and education, merging technologies and blurring the boundaries between the physical, digital, and biological realms. The COVID-19 pandemic has accelerated this process, leading to “the new normal.” This phenomenon is in its early stages in the Argentine context, with a partial and limited adoption of technologies, especially in commercial and administrative areas, particularly in SMEs. To gain a comprehensive understanding of the phenomenon, this exploratory review aims to identify and present available empirical information on the impact of digital transformation on management or business models used by Argentine companies. A scoping review was conducted to describe and map articles published in scientific journals, supported by a PRISMA Diagram. It is concluded that the challenges to initiating digital transformation processes are manifold, emphasizing the need for structural changes in organizations, digital training for workers and professionals, and the promotion of a culture of innovation.